Computerized Self-help Design For Youth Depression Management - Siti Fadzilah Mat Noor; Nor Hidayah Hussain; Tengku Siti Meriam Tengku Wook; Hazura Mohamed; Nur Fazidah Elias; Wan Salwina Wan Ismail; Norhayati Ibrahim; Anuradha Thiagarajan; Norasikin Fabil (Penerbit UKM, 2024)
Indexed by MyCite